The Concept of the “Truth Decay” in a Digital Society (an Analytical Review) - M. N. Grachev (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2020)
The emergence of the “posttruth” phenomenon as the dominance of emotions and opinions over facts, the widespread dissemination of false information, and the rapid growth of fake news in the modern political communication space are the external manifestations of a more complex system of challenges, the basis of which lies in the changed nature of the media environment and ways of processing information by people’s minds, which, in turn, are caused by prevailing political and economic relations. This system of challenges is called “Truth Decay” and characterized by a set of four interconnected and interdependent trends in the contemporary political communication processes: the increase of the contradictions between facts and interpretations of these facts; the erasure of the differences between facts and opinions; the amplification of the opinions and personal points of view influence on the perception of facts; the drop of the mass audience confidence to the sources of information that were previously considered as authoritative. It is obvious that the indicated tendencies were appeared earlier, but their impact on the public consciousness becomes especially more significant and noticeable with the advent of the “digital era”. There is reason to consider that this indicated impact in a certain extent may be due to the premeditated efforts of some political actors pursuing their own interests. The authors are analyzed the recently published results of studies conducted by specialists of the RAND Corporation, which are clearly demonstrated the erosion of the civil discourse and con- vincingly explain it from the standpoint of the “Truth Decay” concept. This research area is innovative for the modern political science and is so far based solely on the analysis of the materials concerned to American realities. However, the authors are believed that the results reached by the scientists from the USA are more general and this conclusions can be used for the study of the modern political communication in processes other countries.